Papua New Guinea Economic Update, January 2021 : Dealing with a Triple Crisis - World Bank (World Bank, Washington, DC, 2021)
In 2020, Papua New Guinea faced three crises: the COVID-19 health emergency, an economic contraction, and political turmoil. The economy contracted by 3.8 percent in 2020 and will rebound by 3.5 percent in 2021. Considering that the economy entered the COVID-19 crisis with a poor record of resilience to external shocks, strengthening macroeconomic management and accelerating structural reforms will be vital. Strengthening public institutions that deliver basic public services, especially during crises, is also important.